Medieval Trade in Central Europe, Scandinavia, and the Balkans (10th-12th Centuries) - Pranke, Piotr, author.
1 online resource.
Keywords: In the historiography of trade in the Middle Ages, there is a wide current of theoretical consideration referring to the ways contemporaries perceived trade. The present work pays specific attention to how trade functioned within the range of the influence of the Ottonian Empire and Byzantium, from the 10th to 12th centuries. This book attempts to verify these concepts in the extensive available source. The manner of circulation of goods and the phenomenon of accumulating goods is a significant product of the present book, demonstrating how imperial influences that perceived through the prism of generative centres on the peripheries of Europe. This volume is the English translation of Handel interregionalny od X do XII wieku. Europa Środkowa, Środkowo-Wschodnia, Półwysep Skandynawski i Półwysep Bałkański. Studium Porównawcze (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika,Torun 2016).